Peran Monitoring Terhadap Peningkatan Kinerja Keuangan di Industri Perbankan Indonesia - Zulfikar, Rudi (Jurnal Ekonomi, 2021)
The purpose of this study was to examine the role of company monitoring on the financial performance of Regional Development Banks (BPD) in Indonesia. The monitoring role is proxied by the characteristics of the Board of Commissioners, the Audit Committee and the Risk Monitoring Committee. Financial performance is measured by Return on Assets (ROA). By purposive sampling, secondary data was selected from 66 annual reports of Regional Development Banks (BPD) for 2017-2019 in Indonesia. The average level of financial performance is at 4.11%. This figure shows that the company's assets to generate profits for shareholders amounted to 4.11%. The regression results show that there is a positive influence on the proportion of independent commissioners on financial performance at Regional Development Banks and there is a positive influence on the size of the risk monitoring committee on financial performance at Regional Development Banks. Other Results The size of the board of commissioners, the size of the audit committee and the number of audit committee meetings have a negative effect. While the control variable, namely company size, has a positive effect in predicting financial performance.